2020
DOI: 10.3390/nu12051469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation with Saccharomyces Boulardii on Academic Examination Performance and Related Stress in Healthy Medical Students: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: In recent years, bacterial probiotic dietary supplementation has emerged as a promising way to improve cognition and to alleviate stress and anxiety; however, yeast probiotics have not been tested. The aim of the present study was to determine whether 30-day supplementation with Saccharomyces boulardii enhances academic performance under stress and affects stress markers. The trial was retrospectively registered at clinicaltrials.gov (NCT03427515). Healthy medical students were randomized to supplement their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 72 publications
1
31
0
2
Order By: Relevance
“…boulardii ( Saccharomyces boulardii , Sb ) has also been found to have probiotic properties ( 32 ). Sb has been extensively tested and widely used in gastroenterology ( 32 , 33 ); however, it is a subject of very little research in neuroscience ( 34 , 35 ), particularly in relation to its serotonergic effect. Intriguingly, fungal probiotics significantly differ from bacterial ones in their biological characteristics, mechanism of action and beneficial properties ( 36 , 37 ), and the effects of probiotic bacteria cannot be easily extrapolated to yeasts ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…boulardii ( Saccharomyces boulardii , Sb ) has also been found to have probiotic properties ( 32 ). Sb has been extensively tested and widely used in gastroenterology ( 32 , 33 ); however, it is a subject of very little research in neuroscience ( 34 , 35 ), particularly in relation to its serotonergic effect. Intriguingly, fungal probiotics significantly differ from bacterial ones in their biological characteristics, mechanism of action and beneficial properties ( 36 , 37 ), and the effects of probiotic bacteria cannot be easily extrapolated to yeasts ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sb has been extensively tested and widely used in gastroenterology ( 32 , 33 ); however, it is a subject of very little research in neuroscience ( 34 , 35 ), particularly in relation to its serotonergic effect. Intriguingly, fungal probiotics significantly differ from bacterial ones in their biological characteristics, mechanism of action and beneficial properties ( 36 , 37 ), and the effects of probiotic bacteria cannot be easily extrapolated to yeasts ( 35 ). Therefore, there is a need to determine the serotonergic effect of yeast probiotics and its potential therapeutic implications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caution is warranted with this study however, since errors in the statistical analysis in the initial manuscript warranted a subsequent correction which significantly altered the initially promising reported outcome (Tran 2019). By far the most common study design for both pre- and probiotics involved following a cohort of selected and unselected university students before, during, and after final exams (Marcos, Warnberg et al 2004, Andersson, Tullberg et al 2016, Culpepper, Christman et al 2016, Kato-Kataoka, Nishida et al 2016, Kato-Kataoka, Nishida et al 2016, Takada, Nishida et al 2016, Karbownik, Kreczynska et al 2020). These studies often only used stress or anxiety as a secondary outcome, focussing on stress-related GI problems or immune performance, mostly with salivary cortisol as the main outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the literature currently does not support their use in reducing anxiety, and two studies reported adverse effects, e.g. increased BAI (Tran, Zhebrak et al 2019) and increased pulse rate (Karbownik, Kreczynska et al 2020).…”
Section: Introductionmentioning
confidence: 99%